GE_GERICHTE C/18903/2016 vom 19. November 2018 - GE Cour de justice (2018)
BAIL À LOYER ; RESTITUTION ANTICIPÉE ; INDEMNITÉ POUR OCCUPATION ILLICITE ; DOMMAGES-INTÉRÊTS | CO.97.al1; CO.257c; CO.267.al1; CO.99.al3; CO.44; CO.264.al1; LCR.9.al1; LCR.9.al2